RANCANGAN MIKRO GAS TURBIN BERBAHAN BAKAR BIOGAS UNTUK PEMBANGKIT TENAGA LISTRIK BIOMASS BERKAPASITAS 2,5 KW, STUDI KASUS:CIPARAY BANDUNG - Kusnadi, Kusnadi; Arifin, Maulana; Darussalam, Rudi; Rajani, Ahmad (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
One of biogas conversion machine which started being used in Indonesia is a micro gas turbine. This study discusses the micro gas turbines fueled by biogas produced from the anaerobic process cow manure. Micro gas turbines are designed to drive electric generators with a capacity of 2.5 kW. The turbine is designed using some supporting components, namely compressor, combustor and turbine. Compressors are used axial compressor then other parameters are designed to meet the needs of the generation of 2.5 kW. Designing the thermal power station is assumed to be 100% methane. Based on the calculation and analysis of further gain the actual compressor 370.80 kJ / kg, combustion chamber heat supply 675.80 kJ / kg, the actual turbine work 612.19 kJ / kg and cycle efficiency of 35.81%. Generating this kind of micro gas turbine has the advantage that, are mobile and have the maintenance and operating costs are cheap. Keywords: micro gas turbines, biogas power plants, the efficiency of the cycle, the flow rate of fuel.